Forecasting the Impact of Climate Change on Apis dorsata (Fabricius, 1793) Habitat and Distribution in Pakistan - Tauheed Ullah Khan; Xiaofeng Luan; Ghulam Nabi; Muhammad Fahad Raza; Arshad Iqbal; Shahid Niaz Khan; Huijian Hu (Insects)
Climate change has led to global biodiversity loss, severely impacting all species, including essential pollinators like bees, which are highly sensitive to environmental changes. Like other bee species, A. dorsata is also not immune to climate change. This study evaluated the habitat suitability of A. dorsata under climate change in Pakistan by utilizing two years of occurrence and distribution data to develop a Maximum Entropy (MaxEnt) model for forecasting current and future habitat distribution. Future habitat projections for 2050 and 2070 were based on two shared socioeconomic pathways (SSP245 and SSP585) using the CNRM-CM6-1 and EPI-ESM1-2-HR-1 global circulation models. Eight bioclimatic variables (Bio1, Bio4, Bio5, Bio8, Bio10, Bio12, Bio18, and Bio19) were selected for modeling, and among the selected variables, the mean temperature of the wettest quarter (Bio8) and precipitation of the warmest quarter (Bio18) showed major contributions to the model building and strongest influence on habitat of A. dorsata. The model estimated 23% of our study area as a suitable habitat for A. dorsata under current climatic conditions, comprising 150,975 km2 of moderately suitable and 49,792 km2 of highly suitable regions. For future climatic scenarios, our model projected significant habitat loss for A. dorsata with a shrinkage and shift towards northern, higher-altitude regions, particularly in Khyber Pakhtunkhwa and the Himalayan foothills. Habitat projections under the extreme climatic scenario (SSP585) are particularly alarming, indicating a substantial loss of the suitable habitat for the A. dorsata of 40% under CNRM-CM6-1 and 79% for EPI-ESM1-2-HR-1 for the 2070 time period. This study emphasizes the critical need for conservation efforts to protect A. dorsata and highlights the species’ role in pollination and supporting the apiculture industry in Pakistan.